2015
DOI: 10.1021/es504259s
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Metal Oxide Nanoparticles in Escherichia coli Correlates with Conduction Band and Hydration Energies

Abstract: Metal oxide nanoparticles (MOx NPs) are used for a host of applications, such as electronics, cosmetics, construction, and medicine, and as a result, the safety of these materials to humans and the environment is of considerable interest. A prior study of 24 MOx NPs in mammalian cells revealed that some of these materials show hazard potential. Here, we report the growth inhibitory effects of the same series of MOx NPs in the bacterium Escherichia coli and show that toxicity trends observed in E. coli parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
139
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(145 citation statements)
references
References 41 publications
6
139
0
Order By: Relevance
“…The observed antibacterial ability with relatively low efficiency can be attributed to the generation of the V 2 O 3 phase on the surface. With regard to sample V3 (V 2 O 3 nanoparticle film), since V 2 O 3 is a strong reductant, it may allow electronic charge flowing between V 2 O 3 nanoparticles and adherent bacteria, 36,37 which thus disrupts the membrane electron transfer and causes oxidative stress and damage to adherent bacteria. For planktonic bacteria, V 2 O 3 holds the potential to react gradually with dissolved oxygen in aqueous solution to form VO 2 The H 2 VO 4 -anions will gradually enter the aqueous solution and account for the observed antiplanktonic bacteria activity.…”
Section: Plausible Antimicrobial Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed antibacterial ability with relatively low efficiency can be attributed to the generation of the V 2 O 3 phase on the surface. With regard to sample V3 (V 2 O 3 nanoparticle film), since V 2 O 3 is a strong reductant, it may allow electronic charge flowing between V 2 O 3 nanoparticles and adherent bacteria, 36,37 which thus disrupts the membrane electron transfer and causes oxidative stress and damage to adherent bacteria. For planktonic bacteria, V 2 O 3 holds the potential to react gradually with dissolved oxygen in aqueous solution to form VO 2 The H 2 VO 4 -anions will gradually enter the aqueous solution and account for the observed antiplanktonic bacteria activity.…”
Section: Plausible Antimicrobial Mechanismmentioning
confidence: 99%
“…20 On the other hand, for planktonic bacteria, as analyzed herein, the intermediate state VO 2 In regard to sample V5 (V 2 O 5 nanoparticle film), V 2 O 5 is a strong oxidant and may be able to extract electrons from the bacteria membrane and disturb the electron-transport chain, thus causing oxidative damage to adherent bacteria. 36,37 It has been reported that the redox activity of V 2 O 5 can be used as a biosensor to detect biological macromolecules in which V 2 O 5 acts as the charge-exchanging catalyst to complete the oxidation-reduction cycle. 41 As for the planktonic bacteria, as discussed earlier, the …”
Section: Plausible Antimicrobial Mechanismmentioning
confidence: 99%
“…These methods provide valuable NMs hazard and toxicity data. Moreover, in addition to the regulation of NMs use, in vivo methods, and reducing, refining, and replacing animal experiment principle (3Rs), in vitro and in silico standards have been proposed for nanotoxicity investigations (Burello 2015; Gajewicz et al 2012;Gong et al 2012;He et al 2013;Ivask et al 2010;Kaweeteerawat et al 2015;Kleandrova et al 2014;McCracken et al 2016;Mortimer et al 2010;Qin et al 2008). For further information about the safety of manufactured nanomaterials, readers are referred to OECD regulations (http://www.oecd.org/science/nanosafety/).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the efforts of many research groups, extensive toxicological data are available for certain nanoparticles (NPs) (Bondarenko et al 2013;Gajewicz et al 2012;Garner et al 2015;Golbamaki et al 2015;Kaweeteerawat et al 2015;Magdolenova et al 2014). However, conflicting results are frequently reported, which are usually attributed to incomplete characterizations of the NMs, different testing conditions, diverse model organisms, and different endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the accumulation of Fe 3 O 4 nanoparticles on the surface of Fe 3 O 4 nanoparticles cell, as shown in Fig. 2b, may contribute to the disruption of cell membrane due to a significant increase in permeability [11].…”
Section: Membrane Damage Assaymentioning
confidence: 99%